Instanton solution for Schwinger production of 't Hooft-Polyakov monopoles - Ho,DL-J; Rajantie,A (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2021)
We present the results of an explicit numerical computation of a novel instanton in Georgi-Glashow SU(2) theory. The instanton is physically relevant as a mediator of Schwinger production of ’t Hooft–Polyakov magnetic monopoles from strong magnetic fields. In weak fields, the pair production rate has previously been computed using the worldline approximation, which breaks down in strong fields due to the effects of finite monopole size. Using lattice field theory we have overcome this limit, including finite monopole size effects to all orders. We demonstrate that a full consideration of the internal monopole structure results in an enhancement to the pair production rate, and confirm earlier results that monopole production becomes classical at the Ambjørn-Olesen critical field strength.